The internal and external centralisation of Capital Markets Union regulatory structures: the case of Central Counterparties (2020)
The aim of this chapter is to study if, how and to what extent the recent reforms of the regulatory framework for central counterparty clearing houses (CCPs) have led to a centralisation of the supervisory authority over the EU financial sector. The reform of the CCP regulation, known as the European Market Infrastructure Regulation (EMIR) was part of the Capital Markets Union (CMU) project. The CMU is a package of regulatory reforms unveiled in 2015 as one of the flagship projects of the Juncker Commission. It has the ambitious goal of deepening, integrating and diversifying the EU financial market, focusing in particular on non-banking segments like bond issuance, corporate bond securitisation, public equity investment, venture capital and credit intermediation by specialised non-bank financial firms (i.e. leasing companies and consumer finance companies) (Quaglia et al. 2016). Implementation of the various CMU proposals has indeed led to a reshaping of the regulatory framework for many financial activities, marking a landmark moment in EU financial regulation. At the same time, this regulatory activity has been contentious, as it has required strengthened cross-border intra-EU and extra-EU regulatory and supervisory cooperation. This is particularly true for the regulation of CCPs, which – as market infrastructure – are a key node of internal market integration, making them an ideal vantage point from which to study regulatory and supervisory centralisation in a horizontal and vertical perspective (Smoleńska 2017).